2021
DOI: 10.1021/acsomega.1c00419
|View full text |Cite
|
Sign up to set email alerts
|

Constructing Hierarchically Porous N-Doped Carbons Derived from Poly(ionic liquids) with the Multifunctional Fe-Based Template for CO2 Adsorption

Abstract: Nitrogen-doped hierarchical porous carbons with a rich pore structure were prepared via direct carbonization of the poly(ionic liquid) (PIL)/potassium ferricyanide compound. Thereinto, the bisvinylimidazolium-based PIL was a desirable carbon source, and potassium ferricyanide as a multifunctional Fe-based template, could not only serve as the pore-forming agent, including metallic components (Fe and Fe 3 C), potassium ions (etching carbon framework during carbonization), and gas generate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 64 publications
0
16
0
Order By: Relevance
“…PET is the most widely used carbon precursor among these polymers due to its wide availability and high carbon content [3]. Poly-ionic liquids (PIL) are also being actively utilized as a potential polymer-based carbon precursor for synthesizing adsorbents [157,158]. The PILs possess high thermal stability (even up to 400 • C), are rich in heteroatoms (e.g., nitrogen), and produce a higher yield of the adsorbent compared to other polymeric precursors [157][158][159].…”
Section: Porous Carbon Synthesis Using Different Precursorsmentioning
confidence: 99%
See 2 more Smart Citations
“…PET is the most widely used carbon precursor among these polymers due to its wide availability and high carbon content [3]. Poly-ionic liquids (PIL) are also being actively utilized as a potential polymer-based carbon precursor for synthesizing adsorbents [157,158]. The PILs possess high thermal stability (even up to 400 • C), are rich in heteroatoms (e.g., nitrogen), and produce a higher yield of the adsorbent compared to other polymeric precursors [157][158][159].…”
Section: Porous Carbon Synthesis Using Different Precursorsmentioning
confidence: 99%
“…A hierarchically porous structure is generally more favorable for adsorbing the CO 2 molecules [158]. Although the narrow micropores are more beneficial than large-sized micropores for CO 2 adsorption (stronger adsorbate-adsorbent interactions) [4,101,188], the mesoporous and microporous structure in a particular adsorbent plays a vital role in improving the mass transfer of CO 2 molecules.…”
Section: The Effect Of Synthesis Procedures On the Development Of Tex...mentioning
confidence: 99%
See 1 more Smart Citation
“…PILs based on bisvinylimidazolium salts were ideal carbon sources, and potassium ferricyanide, with a versatile iron‐based formwork, served as a porogenic agent, with metal components, potassium ions, and gases generated during pyrolysis, and introduced nitrogen atoms to facilitate CO 2 capture. The results showed that NDPC‐1‐800 had better CO 2 adsorption volume and selectivity than NDC‐800, which was directly carbonized from pure PIL 25 . Recently, N‐doped carbon as a metal‐free, low‐cost electrocatalyst for CO 2 RRs has received increasing attention in academic and industrial fields 26 …”
Section: Introductionmentioning
confidence: 99%
“…The results showed that NDPC-1-800 had better CO 2 adsorption volume and selectivity than NDC-800, which was directly carbonized from pure PIL. 25 Recently, N-doped carbon as a metalfree, low-cost electrocatalyst for CO 2 RRs has received increasing attention in academic and industrial fields. 26 Compared with research on nitrogen-doped carbons, there are few studies and literature reports on phosphorus-doped carbons.…”
mentioning
confidence: 99%